2021
DOI: 10.3389/fcimb.2021.625461
|View full text |Cite
|
Sign up to set email alerts
|

The Association of TLR2, TLR3, and TLR9 Gene Polymorphisms With Susceptibility to Talaromycosis Among Han Chinese AIDS Patients in Guangdong

Abstract: BackgroundTalaromycosis (TM) caused by Talaromyces marneffei (T. marneffei) is a growing public health concern. Although Toll-like receptor (TLR) genes play a critical role in the host defense against fungal infection, the influence of polymorphisms in these genes on the susceptibility of acquired immune deficiency syndrome (AIDS) patients to TM remains unknown. This study aims to uncover the associations of single nucleotide polymorphisms (SNPs) in TLR genes with TM susceptibility among patients with AIDS.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Evidence showed that m 6 A levels on TLR2 mRNA was hypermethylated in TM‐infected cells (Figure 3D), but TLR2 expression was downregulated (Figure 3C). TLR2 is located on the cell surface to detect pathogen invasion, and higher expression levels of TLR2 in macrophages were associated with increased TM cytotoxicity and severity 29,30 . To investigate whether YTHDC2 promotes TM replication by altering m 6 A‐mediated TLR2 expression, we first assess the mRNA levels of TLR2 in YTHDC2 knockdown cells under HIV and/or TM infection, as well as the transcriptional level of cytokine factor (TNF‐α) and chemokine factor (IL1‐β).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence showed that m 6 A levels on TLR2 mRNA was hypermethylated in TM‐infected cells (Figure 3D), but TLR2 expression was downregulated (Figure 3C). TLR2 is located on the cell surface to detect pathogen invasion, and higher expression levels of TLR2 in macrophages were associated with increased TM cytotoxicity and severity 29,30 . To investigate whether YTHDC2 promotes TM replication by altering m 6 A‐mediated TLR2 expression, we first assess the mRNA levels of TLR2 in YTHDC2 knockdown cells under HIV and/or TM infection, as well as the transcriptional level of cytokine factor (TNF‐α) and chemokine factor (IL1‐β).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, an investigation of human genetic polymorphisms was undertaken to predict susceptibility against T. marneffei infection. The approach focused on single nucleotide polymorphisms (SNPs) in Toll-like receptor (TLR) genes of Han Chinese with AIDS demonstrated that SNPs within the TLR2, TLR4, and TLR9 genes may contribute to increasing the susceptibility and severity to T. marneffei [105]. Moreover, the presence of anti-IFN-γ autoantibodies in adult-onset acquired immunodeficiency (AOID) was significantly associated with HLA-DRB1*16:02 and HLA-DQB1*05:02 alleles in these patients [41].…”
Section: Host Defense Mechanismsmentioning
confidence: 99%
“…A study using monoclonal antibodies against PRRs on human monocytes to investigate binding to T. marneffei conidia showed that the MR, TLR1, TLR2, TLR4, TLR6, CD14, CD11b and CD18 were all involved in phagocytosis [ 24 ]. Recently, a study in AIDS patients in China linked talaromycosis severity with single-nucleotide polymorphisms in TLR2 but not in TLR3 or TLR9 [ 71 ].…”
Section: Dimorphic Fungal Recognition and Associated Host Responsementioning
confidence: 99%